Penerapan Personal Higiene pada Pengolahan Makanan di Main Kitchen Harris Hotel & Conventions Bundaran Satelit Surabaya - Fahmi Haqiqi Ramadhani; Niken Purwidiani; Any Sutiadiningsih; Sri Handajani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the application of personal hygiene in food processing in the main kitchen of Harris Hotel & Conventions Bundaran Satelit Surabaya. The type of research used is descriptive quantitative, data collection methods with observation and interviews. The results of the study obtained are from the scope of cleanliness with a percentage of 87% so that it is categorized as very good seen from grooming that runs well such as shaving mustaches, shaving beards, cutting nails when they are long and using an apron when working in the kitchen to maintain cleanliness when processing food. From the scope of habits/behaviors, it gets a percentage of 97% so that it is categorized as very good seen from the use of hand gloves when touching food, not wearing work clothes during the trip then work clothes start to be worn in the locker room before entering the kitchen, using safety shoes when working, washing hands before and after work, using a mask when coughing, using napkins or rags that are used separately such as for cleaning the working table and rags for cleaning plates before serving, not wearing jewelry when working, always washing knives when finished to avoid contamination. From the health sector, the percentage of 80% is categorized as very good, seen from the provision of sanitation hygiene training, especially personal hygiene and medical check-up examinations.